Financing and provision of primary health care in Malaysia / Makmor Tumin, Ganeshwaran Kana and Aimi Ahmad Zaki - Tumin, Makmor; Kana, Ganeshwaran; Ahmad Zaki, Aimi (Universiti Teknologi MARA, Shah Alam, 2016)
In spite of being recognised as among the world’s better health system, Malaysia tries to reform its present two-tier health policy, proposing a social health insurance approach. Primary care services in public hospitals are fully subsidised and public-private providers are widely accessible. The aim of this paper is to present Malaysia’s primary care achievements (financial and provision), questioning the social health policy in the process. Data in this paper was gathered from government sources, mainly from the Ministry of Health (MOH) library (including the virtual library) and was compiled mostly through time series, explaining the dynamics of financial and provision of healthcare. The results indicate that Malaysia still spends less despite the relatively impressive achievements although problems such as waiting list remain germane in the system. We conclude that while social health status are largely competitive and the government still spends less, especially following the World Health Organisation (WHO) indicators of health expenditure, the social health insurance proposed in this country could perhaps be at best missed time.